Authenticating wild Piper species (peppers) originating from islands in the Indian Ocean on the basis of morphological, genetic and chemical characteristics. (October 2021) - Weil, Mathieu; Leong PockTsy, Jean Michel; Razafimandimby, Harizoly
Abstract: As demand for pepper is rising to unprecedented levels, gaps in our knowledge are underlined by our inability to reliably distinguish the different species, in particular in the south-western Indian Ocean; this hampers the possibility of developing their economic potential and protect them efficiently. The aim of this study was to characterise two species of Piper (piperaceae) from Madagascar and one from Réunion Island via a multidisciplinary approach combining botany, genetics and chemistry and to propose authentication keys. Morphometric analyses were carried out on 22 quantitative and qualitative descriptors of the leaf and infructescence. Genetic analyses were conducted through DNA extraction, amplification by PCR and sequencing. Chemical analyses used spectrophotometric and chromatographic methods to determine concentrations in piperine and essential oil and describe the chemotypes of the sampled individuals. Our tri-disciplinary approach showed that the three peppers studied are very different from Piper nigrum L. Réunionese Piper borbonense and M3 Malagasy pepper clearly differ from the M1 Malagasy morphotype. Piper borbonense and M3 pepper appear to be closely related; a distinction could possibly be made at the variety (var.) or form (fa.) level on the basis of morphometry and according to piperine content for chemistry. Graphical abstract: Image 1 Highlights: Réunionese Piper borbonense (PB) and Malagasy M3 are distinct from Malagasy M1. PB differs from M3 in denser leaf secondary veins network and more elongate berry. Piper borbonense and M3 are genetically close to one another. Piper borbonense differs from M3 in its lower piperine content. All three wild peppers studied are very different from Piper nigrum .